Seismic and geodetic evidence for grounding‐line control of Whillans Ice Stream stick‐slip events. Issue 2 (24th February 2014) - Pratt, Martin J.; Winberry, J. Paul; Wiens, Douglas A.; Anandakrishnan, Sridhar; Alley, Richard B.
Abstract The tidally modulated, stick‐slip events of Whillans Ice Stream in West Antarctica produce seismic energy from three locations near the grounding line. Using ice velocity records obtained by combining time series from colocated broadband seismometers and GPS receivers installed on the ice stream during the 2010–2011 and 2011–2012 austral summers, along with far‐field seismic recordings of elastic waves, we locate regions of high rupture velocity and stress drop. These regions, which are analogous to "asperities" in traditional seismic fault studies, are areas of elevated friction at the base of the ice stream. Slip events consistently initiate at one of two locations: near the center of the ice stream, where events associated with the Ross Sea high tide originate, or a grounding‐line spot, where events associated with the Ross Sea low tide initiate, as well as occasional high‐tide events following a skipped low‐tide event. The grounding‐line site, but not the central site, produces Rayleigh waves observable up to 1000 km away, through fast expansion of the slip area. Grounding‐line initiation events also show strong directivity in the downstream direction, indicating initial rupture propagation at 1.5 km/s, compared to an average of 0.150 km/s for the entire slip event. Following slip initiation, additional seismic energy is produced from two sources located near the grounding line: first at the downstream end of Subglacial Lake Engelhardt and second toward the farthest downstream extent of the ice stream. This evidence suggests that the stronger, higher‐friction material along the grounding line controls motion throughout the stick‐slip region.